2018
DOI: 10.1177/1533033818762207
|View full text |Cite
|
Sign up to set email alerts
|

Defeating Cancers’ Adaptive Defensive Strategies Using Thermal Therapies: Examining Cancer’s Therapeutic Resistance, Ablative, and Computational Modeling Strategies as a means for Improving Therapeutic Outcome

Abstract: Background:Diverse thermal ablative therapies are currently in use for the treatment of cancer. Commonly applied with the intent to cure, these ablative therapies are providing promising success rates similar to and often exceeding “gold standard” approaches. Cancer-curing prospects may be enhanced by deeper understanding of thermal effects on cancer cells and the hosting tissue, including the molecular mechanisms of cancer cell mutations, which enable resistance to therapy. Furthermore, thermal ablative thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 193 publications
(254 reference statements)
0
21
0
Order By: Relevance
“…This is compared to argon JT based cryosystems where the -20 • C isotherm is reported to penetrate <5 mm in 2 mins and ∼9 mm following 5+ mins of freezing [44,51,52]. Depth of penetration of the -20 • C and -40 • C isotherms are often used as reference points clinically [1,8,9,16,17,22,23]. With the reported minimal lethal temperature for BC in the range of -20 • C, we focused on the -20 • C isotherm as it represents a potential target isotherm for the treatment of BC [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is compared to argon JT based cryosystems where the -20 • C isotherm is reported to penetrate <5 mm in 2 mins and ∼9 mm following 5+ mins of freezing [44,51,52]. Depth of penetration of the -20 • C and -40 • C isotherms are often used as reference points clinically [1,8,9,16,17,22,23]. With the reported minimal lethal temperature for BC in the range of -20 • C, we focused on the -20 • C isotherm as it represents a potential target isotherm for the treatment of BC [46].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, cryolesions do not "grow" post treatment whereas heat-based lesions will increase in size (depth) for several days, clinically resulting in a higher risk of complications [11][12][13][14]. Other benefits include depth of penetration, ability to use in combination with other treatments (adjunctive role), likely improved hemostasis and the ability to target non-resectable tumors [15][16][17][18]. Through percutaneous needles or catheter-based approaches, the delivery of cryoablative doses to tissues not traditionally targeted by the therapy have expanded [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to traditional approaches (surgery, radiotherapy and chemotherapy), thermal therapies are nowadays being increasingly recognized as treatment options for primary cancers, as well as for metastases [14]. In thermal ablation, heating of the tumour tissue to temperatures of about 55–60 °C for short time periods (typically less than 2 min) causes thermal denaturation of proteins and cell membranes, and results in cell death within minutes (via coagulative necrosis) or hours (via apoptosis).…”
Section: Introductionmentioning
confidence: 99%
“…To increase tissue temperatures, usually electromagnetic or ultrasound energy, such as radiofrequency waves (RF), microwaves (MW), laser, or high intensity focused ultrasound (HIFU), is directed at the target tissue. An interstitial or intracavitary antenna can be used for RF/MW, a fiber-optic probe is inserted into the tumour for laser therapy, while in cryoablation tissue freezing is performed via cryoprobes inserted into the tissue [14]. Though minimally invasive, these techniques are difficult to apply to bone tumours, since they require the insertion of a heat (or cold) source directly into bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is an important mechanism for maintaining cellular homeostasis through nutrition recycling and protein quality control. Further evidence has shown that autophagy may be activated during chemotherapy in most tumor cell lines [30]. Autophagy also plays a central role in pharmacological manipulation, and its pathways may serve as therapeutic targets for treating cancer [31].…”
Section: Introductionmentioning
confidence: 99%